A discriminação em Clara dos Anjos, de Lima Barreto, à luz da avaliatividade: uma perspectiva sistêmico-funcional - Brasil, Fabiana Pastore (2012)
This research focuses on socio-racial discrimination found along the novel Clara dos Anjos, by Lima Barreto, examining lexicogrammatical choices made by the author, not only to take a stand on the socio-racial issue, but also to get the reader s sympathy, creating a convincing picture black people s unconsciousness about their own servitude. For this purpose, it examines the question of identity, according to Bucholtz and Hall (2005) and Snow (2001) and the importance of the ideological context, according to Banks (2005). In methodological terms, this study is based on studies of semantic evaluation, an extension of the Interpersonal Metafunction in Systemic-Functional Linguistics (HALLIDAY, 1994, 2004) and on the Appraisal System (MARTIN, 2000) in an approach of Critical Linguistics (FOWLER, 1991). The analysis also has the support of Li (2010), for whom the sociocultural and sociopolitical ideologies are intertwined with language and speech. The author refers to Van Dijk (1993, 1997), who relates the macro notion of ideology to micro notions of discourse and social practices of group members. The study should answer the following questions: (a) which lexicogrammatical choices are made by Lima Barreto to address the socio-racial discrimination issue in the book Clara dos Anjos? (b) how are these choices characterized from the point of view of the Appraisal system? (c) how can Systemic-Functional Linguistics uncover the ideology that involves racial identity in the novel? The research shows that, through negative lexical choices of Appraisal, Lima Barreto seeks to build an ideal reader, able to share his sorrows, of a life marked by socio-racial discrimaination